Risks of cattle babesiosis (Babesia bovis) outbreaks in a semi-arid region of Argentina - Morel, Nicolas; Mastropaolo, Mariano; Torioni, Susana Marta; Signorini, Marcelo; Mangold, Atilio Jose (Elsevier, 2019)
The epidemiology of Babesia bovis was studied in terms of enzootic stability/instability and husbandry and abiotic factors influencing B. bovis transmission rate in northeastern Santiago del Estero province, Argentina. The area is of limited suitability for its only vector in Argentina, the tick Rhipicephalus microplus. The proportion of calf herds in a state of enzootic stability/instability to B. bovis was determined and husbandry practices and abiotic factors associated with variations in B. bovis transmission rates were explored using a cross-sectional observational study design. Daily probability of infection (inoculation rate, h) with B. bovis was calculated from age-specific seroprevalence via ELISAi in 58 herds of 4.5–8.5-month-old calves. Herds were considered to be in enzootic instability (EI) when h < 0.005, and therefore inferred to be at risk of babesiosis outbreaks. Husbandry practices associated with differences in B. bovis transmission were analyzed using generalized linear models. Sixty-two percent of herds were found to be in an EI situation for B. bovis. Calves raised exclusively on permanent pastures –where higher cattle density is achieved– were exposed to higher B. bovis inoculation rates (h = 0.0063, 95% CI 0.0032-0.0123) than those reared under forage combinations (h = 0.0024, 95% CI 0.0011-0.0051) (P =  0.05). In addition, calves from herds located in the area of intermediate suitability for R. microplus development were more likely to become infected with B. bovis (h = 0.0067, 95% CI 0.0037-0.0121) than those reared in the ecologically unfavorable area for the vector (h = 0.0023, 95% CI 0.0010-0.0049) (P =  0.02). Neither the frequency of treatment with acaricides nor the use of long-acting acaricides to control R. microplus influenced the inoculation rate (P =  0.99 and P =  0.26, respectively). This result indicates that current R. microplus control schemes are not effective in reducing B. bovis transmission. Enzootic instability still prevails in the study area despite the drastic changes occurred in cattle production system. However, 38% of herds did reach enzootic stability; therefore, a specific epidemiological status cannot be assumed at a regional level. Yearly determination of the immunological status of each calf cohort is considered a proper approach to decision-making in vaccination against B. bovis.